Pentingnya Pendidikan Akhlak Bagi Anak Di Era Digital SDN 3 Lamangga - Nudin Nudin; La ode Jirman; Wahid Wahid; Nur Wahyuni; Waode Hasrini; Muh. Fahrun Syarifuddin (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
The purpose of community service activities is to provide information to students regarding the importance of moral education for children in the digital era. Moral cultivation for children is very important both in the family, school and community. In this era, which we often call the millennial era, there are often moral deviations for the nation's children with rampant moral damage, for that we as educators fix the cultivation of children's character and morals